2017
DOI: 10.1371/journal.pone.0176350
|View full text |Cite
|
Sign up to set email alerts
|

No-touch radiofrequency ablation using multiple electrodes: An in vivo comparison study of switching monopolar versus switching bipolar modes in porcine livers

Abstract: ObjectiveTo evaluate the in vivo technical feasibility, efficiency, and safety of switching bipolar (SB) and switching monopolar (SM) radiofrequency ablation (RFA) as a no-touch ablation technique in the porcine liver.Materials and methodsThe animal care and use committee approved this animal study and 16 pigs were used in two independent experiments. In the first experiment, RFA was performed on 2-cm tumor mimickers in the liver using a no-touch technique in the SM mode (2 groups, SM1: 10 minutes, n = 10; SM2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…Recently, Chang et al ( 24 55 ) assessed the feasibility and optimal protocol of the “no-touch” ablation technique and evaluated both the switching monopolar mode as well as switching bipolar mode for “no-touch” ablation. In an ex vivo study that used a bovine liver, both switching monopolar and switching bipolar modes were demonstrated to be feasible for “no-touch” ablation.…”
Section: Multiple-electrode Rfamentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Chang et al ( 24 55 ) assessed the feasibility and optimal protocol of the “no-touch” ablation technique and evaluated both the switching monopolar mode as well as switching bipolar mode for “no-touch” ablation. In an ex vivo study that used a bovine liver, both switching monopolar and switching bipolar modes were demonstrated to be feasible for “no-touch” ablation.…”
Section: Multiple-electrode Rfamentioning
confidence: 99%
“…In addition, the distance between the electrode and ablation zone margin of the switching bipolar mode was significantly smaller than that of the switching monopolar mode (1.39 cm vs. 1.86 cm, p < 0.001) as RF energy can be more focused between two electrodes ( 55 ). Chang et al ( 24 ) also assessed the incidence of adjacent organ injury during the “no-touch” ablation technique in their in vivo study using a porcine liver. They found that the frequency of adjacent organ injury after switching bipolar mode “no-touch” RFA was significantly lower than that after switching monopolar mode “no-touch” RFA (23.1% vs. 69.2%, p = 0.021).…”
Section: Multiple-electrode Rfamentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, mbRFA has further been extended to no-touch mbRFA, where direct contact with malignant tissue is avoided by placing multiple electrodes around the tumour. Studies showed that no-touch mbRFA reduces the risk of needle track seeding and moreover, is able to assure an adequate peritumoral safety margin 9 11 . As larger ablation areas are achieved, no-touch mbRFA is also becoming a promising option for the curative treatment of HCC > 5 cm 12 14 .…”
Section: Introductionmentioning
confidence: 99%
“…There has been a surge in popularity in the use of bipolar radiofrequency ablation (bRFA) for treating liver cancer, as evident by the number of research studies that have been published over the past 5 years 1‐6 . Bipolar radiofrequency ablation differs from monopolar RFA (mRFA), in that the technique does not make use of grounding pads in order to complete the electrical circuit.…”
Section: Introductionmentioning
confidence: 99%